Hubungan Body Shaming dan Toxic Friendship dengan Interaksi Sosial pada Mahasiswa Keperawatan di Universitas Indonesia Maju - Derelah Putri Pratiwi; Indri Sarwili (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Positive social interaction among nursing students can be disrupted by Toxic Friendship and Body Shaming, which affect empathy, communication, and the quality of nursing care in the future. This study aims to analyze the correlation between Body Shaming and Toxic Friendship with social interaction among Nursing Students at Universitas Indonesia Maju in 2025. The research method used was quantitative with a descriptive correlational design and a cross-sectional approach. A cluster sampling technique was applied, involving 82 respondents. Data were collected using social interaction, Body Shaming, and Toxic Friendship questionnaires measured with a 5-point Likert scale. Data analysis was performed using Pearson correlation. The results showed that: (1) the majority of respondents had a moderate level of Body Shaming, with 60 students or 73.2%; (2) the majority of respondents had a high level of Toxic Friendship, with 52 students or 63.4%; (3) there was a significant relationship between Body Shaming and social interaction among Nursing Students at Universitas Indonesia Maju with a p-value of 0.00 < 0.05; and (4) there was a significant relationship between Toxic Friendship and social interaction among Nursing Students at Universitas Indonesia Maju with a p-value of 0.00 < 0.05. The conclusion is that there is a relationship between Body Shaming and Toxic Friendship with social interaction. The study suggests socializing the impacts of Body Shaming and Toxic Friendship.